MOTIVASI KERJA DAN KINERJA PEGAWAI KANTOR DINAS KESEHATAN ACEH - Deddy Iskandar; Mukhlis Yunus; M. Shabri Abd Majid (FEB - Unsyiah, 2018)
The study aims to investigate the effect of leadership style, education training, and incentive on work motivation and their impact on the employee’s performance of Aceh health offices. The data collection is conducted by distributing the questionnaire to 213 officers of the office which is selected by working-based proportional methods. Then, the data was analyzed by statistical means of structural equation model (SEM). The study found that the leadership style, education training, and incentives have a positive and significant effect on the performance and work motivation of the employee of Aceh health offices. The work motivation mediates the effect of the three exogenous variable on the employee’s performance. The mediation effect is a partial mediating